ANALISIS KOINTEGRASI BURSA SAHAM CINA DAN BURSA SAHAM ASEAN 5 - Khairani Syafril; Dewi, Andrieta Shintia (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
COVID-19 was first confirmed on December 31, 2019, not only affecting health conditions, but alsoreducing the global economy. This is important for investors who diversify internationally who expectgood risk and portfolio returns. This study aims to analyze the presence or absence of cointegration of theChinese stock exchange and the ASEAN 5 stock exchange. With non-probability sampling methods andpurposive sampling techniques, the sample of this study is daily data on stock market indices in China andASEAN for the period January 1, 2013-31 December 2020. Data analysis used cointegration test whichconsists of Augmented Dickey-Fuller (ADF) Unit Root Test and Engle Granger Cointegration Test. Theresults of this study indicate that the Chinese Stock Exchange (SSECI) is co-integrated with the SingaporeStock Exchange (STI) at the 1%, 5%, and 10% significance levels, and the Malaysia Stock Exchange(KLSEI) at the 10% level. However, it is not co-integrated with the Indonesian Stock Exchange (IHSG)and Thailand (SETI) and the Philippines (PSEI) at the 1%, 5% and 10% significance levels and KLSEI atthe 1% and 5% levels. Based on the results of this study, it is hoped that it can become a reference forinterested parties to find out the long-term relationship between these stock exchanges, especially toadjust to the conditions provided by COVID-19